Nutrition Assessment Survey of School Children of Dharwad and Haliyal Taluks, Karnataka State, India - Chandra, KR Pravin; Padennavar, Uma M; Sadashivappa, T; Prabhakara, GN (Kathmandu University Journal of Science, Engineering and Technology, 2006)
This study was undertaken to find out the magnitude of the problem of undernutrition among the rural school-going children of ages 4 to 14 years and also to identify the epidemiological factors influencing the nutritional status. All 1808 school-going children of 49 villages of Dharwad and Haliyal taluks were included in the study undertaken during Mar-Apr 2005. Systematic random sampling was applied, and 557 children were studied for nutritional assessment. Both the criteria for spotting undernutrition, namely using the WHO/Govt. of India Road to Health card and also the CDC 2000 Standard for BMI for the given age and sex, were followed. The morbidity rate in the universe was 62.9%, and the nutrition-related disorders rate was 59.4%. The anthropometric methods spotted 44.4% of children as underweight/having lean BMI. Nutrition-related disorders were not related to either the father’s or the mother’s literacy nor were they related to the type of occupation of the father. They were associated with the presence of underweight/lean body mass index (p<0.01). More boys than girls had nutrition-related disorders (p<0.05). Backward Hindus (p<0.001) as well as Muslims and Christians had more nutrition-related disorders than forward Hindu children (p<0.05). The literacy status was higher among forward Hindu parents than backward Hindus (p<0.02) and least among Muslims (p<0.05). The backward community children had a better weight for age/BMI profile than forwards (p<0.005). Higher BMI among the Siddhi community, a backward community originating from Arab slave trade from Africa living in the northeastern districts of Karnataka and Goa, is documented in another one or two studies of this kind. The usefulness of WHO/GOI Road to Health card and the CDC-2000-BMI Standards for Nutritional Surveillance of school-age children can yield higher dividends before clinical methods pick up or spot the nutrition-related disorders. Periodic deworming, anti-anemia measures, nutrition education in addition to hygiene education, and vitamin A supplementation in school-age up to 14 years are recommended. Backward communities including the Siddhi community need to be targeted. Literacy is not enough; what is needed is nutrition education of the parents of the school-age children.